Organic and inorganic bromine measurements around the extratropical tropopause and lowermost stratosphere (Ex-LMS): Insights into transport pathways and total bromine - Rotermund, Meike; Bense, Vera; Schuck, Tanja; Vogel, Bärbel; Zahn, Andreas; Pfeilsticker, Klaus; Chipperfield, Martyn; Engel, Andreas; Grooß, Jens-Uwe; Hoor, Peter; Hüneke, Tilman; Keber, Timo; et al. (2021)
We report on measurements of total bromine (Br tot ) in the upper troposphere and lower stratosphere (UTLS) taken from the German High Altitude and LOng range research aircraft (HALO) over the North Atlantic, Norwegian Sea and north-western Europe in September/ October 2017 during the WISE (Wave-driven ISentropic Exchange) research campaign. Br tot is calculated from measured total organic bromine (Br org ) (i.e., the sum of bromine contained in CH 3 Br, the halons and the major very short-lived brominated substances) added to inorganic bromine (Br y inorg ), evaluated from measured BrO and photochemical modelling. Combining these data, the weighted mean [Br tot ] is 19.2 ± 1.2 ppt in the extratropical lower stratosphere (Ex-LS) of the northern hemisphere. The inferred average Br tot for the Ex-LS is slightly smaller than expected for the middle stratosphere in 2016 (~19.6 ppt (ranging from 19-20 ppt) as reported by the WMO/UNEP Assessment (2018)). However, it reflects the expected variability in Br tot in the Ex-LS due to influxes of shorter lived brominated source and product gases from different regions of entry. A closer look into Br org and Br y inorg as well as simultaneously measured transport tracers (CO, N 2 O, .) and an air mass lag-time tracer (SF 6 ), suggests that a filament of air with elevated Br tot protruded into the extratropical lowermost stratosphere (Ex-LMS) from 350-385 K and between equivalent latitudes of 55-80˚N (high bromine filament – HBrF). Lagrangian transport modelling shows the multi-pathway contributions to Ex-LMS bromine. According to CLaMS air mass origin simulations, contributions to the HBrF consist of predominantly isentropic transport from the tropical troposphere (also with elevated [Br tot ] = 21.6 ± 0.7 ppt) as well as a smaller contribution from an exchange across the extratropical tropopause which are mixed into the stratospheric background air. In contrast, the surrounding LS above and below the HBrF has less tropical tropospheric air, but instead additional ...